Experimental and Numerical Investigation on Thermophysical Properties of Hydrocarbon Liquid Mixtures using Krishnan-Laddha and Jouyban-Acree Models at Various Temperatures - R., Ramesh; T. K., Thanusha; M. Y. M., Yunus; K., Ramesh (2016)
The thermophysical properties such as density and viscosity of binary liquid mixtures were determined experimentally over the entire composition range at 303.15K, 308.15K and 313.15K. The experimentally determined thermophysical properties of the binary liquid mixtures were used to calculate the excess molar volume VE and viscosity deviations Δη with two hydrocarbons bromobenzene and ethylbenzene. The excess thermophysical properties of liquid mixtures provide additional information regarding molecular interactions. The calculated excess volumes, VE and deviations in viscosities, Δη exhibited positive and negative values respectively over the whole range of composition in both binary systems. The Krishnan-Laddha and Jouyban-Acree Models were used to correlate deviations in viscosities, Δη, to derive the binary coefficients and standard deviations of these systems. The fitted outcomes and the calculated data clearly indicated that weak interactions present in two mixtures. It is mainly because of the number and position of methyl groups existing in these aromatic hydrocarbons. It can be concluded that the data found with the values fitted by the corresponding Krishnan-Laddha and Jouyban-Acree models gives high degree of precision.